(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Purpose: Obesity is a common health problem in both developed and developing countries. BMI is commonly used to identify obesity. However, there is increasing evidence that the relationship between BMI and BF% differs among various ethnicities. The main objectives of this study are (1) to evaluate the correlation between BF% as determined by BIA, DEXA, Deuterium oxide (D2O) and BMI, (2) to assess the accuracy of currently used WHOÅLs BMI cut-off points to identify overweight and obesity among Syrian women. Material and Methods: A total of 908 healthy Syrian women aged 18-60 years participated in this study. Weight, height, BMI, BF% assessed by BIA and DEXA, and D2O have been determined. Results: BF% results obtained by BIA and DEXA, and D2O revealed strong correlations. BMI showed a statistically significant correlation with BF% determined by BIA, DEXA and D2O. Obesity when defined as BMI ≥ 30 and as BF% > 35% (derived from BIA, DEXA and D2O) classified 43%, 52.5%, 75.9% and 72.7% of women as obese, respectively. ROC analysis defined BMI cut-off points for overweight and obesity of 22.5 and 25.7, respectively. Using the new BMI cut-off point, the prevalence of obesity among Syrian women was increased by 24%. Conclusions: The current BMI cut-off points recommended by WHO underestimate the prevalence of overweight and obesity among Syrian women. Our data suggests that it is important to lower the proposed WHOÅLs BMI cut-off points for the Syrian women.